Efficiency improvement of PCDTBT solar cells with silver nanoparticles - Parlak, Elif Alturk; Tumay, Tulay Asli; Tore, Nesrin; Sarioglan, Serife; Kavak, Pelin; Turksoy, Figen (ELSEVIER, 2013)
We synthesized silver nanoparticles (Ag NPs) with particle sizes similar to 6 nm, and also investigated the effect of Ag NPs on the performance of polymer solar cells. It is seen that Ag NPs improved power conversion efficiency (PCE) of poly[N-9 ''-hepta-decanyl-2,7-carbazole-alt-5,5-(4',7'-di-2-thieny1-2',1',3'-benzothiadiazole) (PCDTBT) solar cells. PCE increased from 0.65 to 1.72 with incorporation of Ag NPs. Hole and electron recombination time (tau(n)) was calculated with impedance spectroscopy as 0.4 ms for PCDTBT solar cells with nanoparticles and 1.26 ms for PCDTBT solar cells without nanoparticles. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: PCDTBT; Organic solar cells; Ag nanoparticles; Impedance; ABSORPTION; Energy & Fuels; Materials Science; Physics